Cardiotoxicity Associated with Gemcitabine: Literature Review and a Pharmacovigilance Study - Marc Hilmi; Stéphane Ederhy; Xavier Waintraub; Christian Funck-Brentano; Ariel Cohen; Aurore Vozy; Bénédicte Lebrun-Vignes; Javid Moslehi; Lee S. Nguyen; Joe-Elie Salem (MDPI AG, 2020)
Background: Gemcitabine is a nucleoside analog, widely used either alone or in combination, for the treatment of multiple cancers. However, gemcitabine may also be associated with cardiovascular adverse-drug-reactions (CV-ADR). Methods: First, we searched for all cases of cardiotoxicity associated with gemcitabine, published in MEDLINE on 30 May 2019. Then, we used VigiBase, the World Health Organization's global database of individual case safety reports, to compare CV-ADR reporting associated with gemcitabine against the full database between inception and 1 April 2019. We used the information component (IC), an indicator value for disproportionate Bayesian reporting. A positive lower end of the 95% credibility interval for the IC (IC025) ≥ 0, is deemed significant. Results: In VigiBase, 46,898 reports were associated with gemcitabine on a total of 18,908,940 in the full database. Gemcitabine was associated with higher reporting for myocardial ischemia (MI, n: 119), pericardial diseases (n: 164), supraventricular arrhythmias (SVA, n: 308) and heart failure (HF, n: 484) versus full database with IC025 ranging between 0.40 and 2.81. CV-ADR were associated with cardiovascular death in up to 17% of cases. Conclusion: Treatment with gemcitabine is associated with potentially lethal CV-ADRs, including MI, pericardial diseases, SVA and HF. These events should be considered in patient care and clinical trial design.